Antidiarrheal potential of standardized extract of Rhododendron arboreum Smith flowers in experimental animals - Verma, Neeraj (Medknow Publications & Media Pvt Ltd, 2011)
OBJECTIVE: To investigate standardized ethyl acetate fraction of Rhododendron arboreum (EFRA) flowers for antidiarrheal activity in experimental animals. MATERIALS AND METHODS: A simple sensitive high performance thin layer chromatography (HPTLC) method was used for the determination of hyperin in EFRA. The standardized fraction was investigated for castor oil, magnesium sulfate-induced diarrhea, measurement of gastrointestinal transit using charcoal and castor oil-induced enteropooling. RESULTS: The concentration of hyperin in flowers of R. arboreum was found to be 0.148% by HPTLC. Oral administration of EFRA at 100, 200 and 400 mg/kg exhibited dose-dependent and significant (P<0.05-0.001) antidiarrheal potential in castor oil and magnesium sulfate-induced diarrhea. EFRA at doses of 100, 200 and 400 mg/kg also produced significant (P<0.05-0.001) dose-dependent reduction in propulsive movement in castor oil-induced gastrointestinal transit using charcoal meal in rats. EFRA was found to possess an antienteropooling in castor oil-induced experimental animals by reducing both weight and volume of intestinal content significantly. CONCLUSION: These findings demonstrate that standardized ethyl acetate fraction of R. arboreum flowers has potent antidiarrheal activity thus justifying its traditional use in diarrhea and have great potential as a source for natural health products.